The Effect of Some Lean Production Tools in selecting a Mass Customization Strategy - هادي, عفاف حسن; عبد الرزاق, نور قصي (Journal of Economics and Administrative Sciences, 2018)
The research aims to indicate the relationship between lean production tools included seven {constant improvement , and Just in time (JIT), and the production smoothing , and quality at the source, and standardized work, Visual management, and activities 5S }  and  Mass Customization strategy for the model (Pine & Gilomer, 1997) {collaborative, adaptive, cosmetic, transparent}, as well as providing a conceptual framework and applied for variables search to clarify how they will choose a Mass Customization strategy through the lean production tools, , and recognize the reality of the practices of Iraqi industries in such a field. Moreover, aims to highlight the positive aspects that accrue to companies as a result of reliance on modern technologies and systems in production and a rapid response to the needs and desires of customers.         It was the application in Al-Asbaagh Al-Hadetha industries company and the Iraqi company for carton manufacturing and trade and supplies, it was used questionnaire to collect data from the research sample consisting of 58 people from the employees of the two companies , There positions functional were (Administrator of the Commissioner, the Director, Deputy Director, technical supervisor, head of observers) and used the methods of statistical analysis (descriptive statistics , correlation analysis , regression analysis ) to analyze the questionnaire and the results showed the existence of a correlation between lean production tools and Mass Customization strategy  , as well as having an impact also among the two companies and prove all the research hypotheses. Recommendations have been proposed in the light of this , the most important benefit from the availability of lean production tools to enhance Mass Customization strategies and strategic choice for being more cooperative strategies appropriate for context two companies Alambhuthtin the work